Literatura e jornalismo : uma análise de “Um dia no cais”, de João Antônio - Lopes, Leandro de Oliveira (2017)
"Um dia no cais", by João Antônio, was firstly published in the magazine Realidade under the categorization of "short story-report". This designation makes us suppose a mixture, in text, of two different textual genres originated from literature and journalism: the short story and the story-report. This study investigates the textual resources that allowed the term, unknow of at that time, to be created and designated to the aforementioned text. Besides, our aim is to discuss the elements that approach the term and, at the same time, make it distance it from an assertive use above its supposed “subgenre” status. To get the results, we used theoretical concepts that define both short story and report in such a way to intersect them. And in order to consider the environment and the context in this analysis, we take the magazine Realidade and the conditions of Brazil (military dictatorship and the incipient development of a Brazilian cultural industry) into consideration at the time of the publication of the text in question, also intending to understand the emergence of this term that still characterizes "Um dia no cais" as the first Brazilian "short story-report".